2013
DOI: 10.1016/j.freeradbiomed.2013.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine quinone modifies and decreases the abundance of the mitochondrial selenoprotein glutathione peroxidase 4

Abstract: Oxidative stress and mitochondrial dysfunction are known to contribute to the pathogenesis of Parkinson's disease. Dopaminergic neurons may be more sensitive to these stressors because they contain dopamine (DA), a molecule that oxidizes to the electrophilic dopamine quinone (DAQ) which can covalently bind nucleophilic amino acid residues such as cysteine. The identification of proteins that are sensitive to covalent modification and functional alteration by DAQ is of great interest. We have hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 67 publications
2
46
0
Order By: Relevance
“…Previous in vitro studies have identified various protein targets, including α-synuclein (Bisaglia et al, 2007(Bisaglia et al, , 2010Marques andOuteiro, 2012), parkin (LaVoie et al, 2005), DJ-1 (Girotto et al, 2012), tyrosine hydroxylase , superoxide dismutase 2 (SOD2) (Belluzzi et al, 2012), glutathione peroxidase 4 (GPx4) (Hauser et al, 2013), and a variety of mitochondrial proteins (Van Laar et al, 2009). However, the in vivo protein targets for quinone modification, particularly proteins with increased quinone modification in aged SN, were completely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies have identified various protein targets, including α-synuclein (Bisaglia et al, 2007(Bisaglia et al, , 2010Marques andOuteiro, 2012), parkin (LaVoie et al, 2005), DJ-1 (Girotto et al, 2012), tyrosine hydroxylase , superoxide dismutase 2 (SOD2) (Belluzzi et al, 2012), glutathione peroxidase 4 (GPx4) (Hauser et al, 2013), and a variety of mitochondrial proteins (Van Laar et al, 2009). However, the in vivo protein targets for quinone modification, particularly proteins with increased quinone modification in aged SN, were completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…While previous in vitro studies were mostly based on educated guess or labeling isolated mitochondria or cultured cells with 14 C-dopamine (Belluzzi et al, 2012;Bisaglia et al, 2007Bisaglia et al, , 2010Girotto et al, 2012;Hauser et al, 2013;; LaVoie et al, 2005; Marques and Outeiro, 2012; Van Laar et al, Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that dopamine o ‐quinone forms adduct with mitochondrial glutathione peroxidase 4 (Hauser et al . ).…”
Section: Dopamine O‐quinone Aminochrome and 56‐indolequinone Metabomentioning
confidence: 97%
“…), mitochondrial glutathione peroxidase 4 (Hauser et al . ); dopamine transporter (Whitehead et al . ); quinoprotein adducts (Wang et al .…”
Section: Dopamine Oxidation To Ortho‐quinonesmentioning
confidence: 99%
“…DJ‐1, which is associated with a recessive form of PD, regulates translation of GPx4 , and oxidation of DJ‐1 increases GPx4 synthesis . Oxidation of dopamine to dopamine quinone, conversely, decreases GPx4 following modification with quinone residues . This could also explain the decrease in GPx1 and GPx4 by methamphetamine in a dopaminergic cell model .…”
Section: Parkinson's Diseasementioning
confidence: 98%